Legal Protection of Copyright for the Literary Script I La Galigo as Communal Intellectual Property - Mendila, Nelson (Universitas Ekasakti, 2024)
This research aims to examine the legal protection of copyright for the literary script I La Galigo as communal intellectual property. The main issues addressed in this study are the implementation of legal measures to protect the I La Galigo manuscript, which holds high cultural and historical value, and whether this manuscript can be categorized as communal intellectual property. The research employs a normative-empirical legal approach, combining normative analysis of legislation with empirical studies on the application of law in practice. The analysis results indicate that the I La Galigo manuscript receives legal protection as part of copyright recognized by law, and the Indonesian government has taken steps to protect copyright and traditional knowledge, including this manuscript. This protection is further supported by UNESCO's international recognition as a Memory of the World. Additionally, the I La Galigo manuscript can be categorized as communal intellectual property due to its collective ownership and value for the Bugis community in South Sulawesi. The study emphasizes the importance of comprehensive and effective legal protection for traditional cultural expressions like the I La Galigo manuscript. More detailed regulations and better implementation are needed to ensure optimal protection for this communal intellectual property. The study concludes that strengthening regulations and raising awareness of the importance of cultural heritage preservation are crucial to safeguarding and protecting the I La Galigo manuscript as part of communal intellectual property.